2011
DOI: 10.1002/zoo.20311
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of adrenocortical function in Florida manatees (Trichechus manatus latirostris)

Abstract: The study objectives were to determine the predominant manatee glucocorticoid; validate assays to measure this glucocorticoid and adrenocorticotropic hormone (ACTH); determine diagnostic thresholds to distinguish physiological vs. pathological concentrations; identify differences associated with sex, age class, female reproductive status, capture time, and lactate; and determine the best methods for manatee biologists and clinicians to diagnose stress. Cortisol is the predominant manatee glucocorticoid. IMMULI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 38 publications
(53 reference statements)
0
12
0
Order By: Relevance
“…The high lactate concentrations are indicative of lactic acidosis as a result of muscular exertion and struggle related to the capture event (Harvey et al, 2007). Lactate concentrations are also positively correlated with cortisol and ACTH concentrations, indicators of chronic and peracute stress, respectively (Tripp et al, 2010).…”
Section: Lactate and Respiration Ratementioning
confidence: 98%
See 1 more Smart Citation
“…The high lactate concentrations are indicative of lactic acidosis as a result of muscular exertion and struggle related to the capture event (Harvey et al, 2007). Lactate concentrations are also positively correlated with cortisol and ACTH concentrations, indicators of chronic and peracute stress, respectively (Tripp et al, 2010).…”
Section: Lactate and Respiration Ratementioning
confidence: 98%
“…A peracute stress response in wild manatees as a result of the capture and handling process has been documented by assaying for adrenocorticotropic hormone (ACTH) concentrations in plasma (Tripp et al, 2010). While capture-related deaths are rare, field biologists encounter animals during research captures and rescues with signs of bradycardia, apnea, hyperthermia, and hypothermia when compared to healthy resting individuals in a captive setting (Scholander & Irving, 1941;Gallivan et al, 1983;Irvine, 1983;Bossart, 2001;Murphy, 2003).…”
Section: Introductionmentioning
confidence: 98%
“…The blood smears were stored at 4°C. The samples were used to determine plasma cortisol using an automated chemiluminescent EIA (Immulite 1000 Cortisol kits, sensitivity 0.2 μg/dL detected on an Immulite 1000 Analyser, Siemens Medical Solutions Diagnostics, Gwynedd, UK; assay validated by Tripp et al, 2010), blood urea using a kinetic UV test (OSR6134, ±0.35 at 7.75 mmol/L, Olympus AU400 Analyser, Life and Materials Science Europa GmBH, Hamburg, Germany), and a full blood count.…”
Section: Experimental Protocolmentioning
confidence: 99%
“…Therefore, ACTH is expected to be preferred to cortisol as an indicator of peracute stress when sample collections occur immediately following exposure to the stress event. This has been confirmed in the Florida manatee (Tripp et al, 2010). Further, studies in marine mammals have shown that ACTH elicits a greater magnitude of the mineralocorticoid aldosterone than it does in terrestrial mammals (St. Aubin & Dierauf, 2001).…”
Section: Introductionmentioning
confidence: 63%
“…Adrenocorticotropic Hormone (ACTH) and related hormones have been assessed in managed-care and free-ranging bottlenose dolphins (Tursiops truncatus) and other marine mammals as measurements of the stress response (Ortiz & Worthy, 2000;Forney et al, 2002;Schmitt et al, 2010;Tripp et al, 2010;Houser et al, 2011). The role ACTH plays in the adrenal mediated response in bottlenose dolphins is similar to that in other mammals (St. Aubin & Dierauf, 2001).…”
Section: Introductionmentioning
confidence: 95%